(untitled) (Comprehensive Journal of Science, 2026)
Thermoelectric materials have attracted sustained scientific interest due to their ability to directly convert heat into electrical energy, offering promising solutions for energy recovery and sustainability. This descriptive study aims to provide a comprehensive overview of the current state of thermoelectric materials by synthesizing recent literature without experimental intervention. The review highlights the principal limitations reported in the field, including low conversion efficiency, thermal and chemical instability, material toxicity, and high production costs. It further describes prevailing research trends, with particular attention to nanostructured systems, hybrid composites, environmentally friendly materials, and topological thermoelectrics. International applications of thermoelectric technologies are descriptively examined across industrial waste heat recovery, transportation systems, aerospace applications, and wearable devices. Within this context, the study discusses the potential relevance of thermoelectric systems for energy diversification in developing regions, such as Libya, especially in decentralized, hybrid, and off-grid energy scenarios. Finally, the review outlines future research directions frequently identified in the literature, including multiscale modeling, interface and defect engineering, sustainable synthesis routes, and integrated device design. By consolidating existing knowledge, this descriptive review aims to clarify the current research landscape and support informed future investigations in thermoelectric materials.